Is standard costing obsolete? Empirical evidence from Malaysia - Sulaiman, Maliah; Nik Ahmad, Nik Nazli; Mohd Alwi, Norhayati (Emerald Group Publishing Limited, 2005)
Purpose – Many authors have predicted that the shorter product life cycles, advanced manufacturing technologies, decreasing emphasis on labour in the production process, and global competition may lead to the demise of standard costing. This exploratory study aims to provide empirical evidence on the extent to which companies in Malaysia use standard costing. It also examines the differences in the use of such techniques between local Malaysian ﬁrms and Japanese afﬁliates.